Modified Sijunzi decoction can alleviate cisplatin-induced toxicity and prolong the survival time of cachectic mice by recovering muscle atrophy. (6th April 2019) - Chen, Jing-Ming; Yang, Ting-Ting; Cheng, Tai-Shan; Hsiao, Ting-Fen; Chang, Peter Mu-Hsin; Leu, Jyh-Yih; Wang, Feng-Sheng; Hsu, Shih-Lan; Huang, Chi-Ying F.; Lai, Jin-Mei
Abstract: Ethnopharmacological relevance: Sijunzi decoction is a well-known traditional Chinese medicine (TCM) commonly used for invigorating vital energy and for the enhancement of immunity. Modified Sijunzi decoctions have been extensively used to treat cachexia and improve the quality of life of cancer patients undergoing chemotherapy. Aim of the study: This study was aimed to provide comprehensive evidence for the anti-cachectic effect of a modified Sijunzi decoction (Zhen-Qi; ZQ-SJZ) and characterize its anti-cachectic mechanism, especially in cisplatin-induced muscle atrophy. Materials and methods: We employed a Lewis lung carcinoma (LLC)-induced cancer cachectic mouse model to demonstrate the anti-cachectic effect of ZQ-SJZ. Moreover, we provided an in vitro C2C12 myotube formation model to investigate the effect of ZQ-SJZ in hampering cisplatin-induced muscle atrophy. Results: The administration of ZQ-SJZ can recover tumor- and/or cisplatin-induced body weight loss, intestinal mucosal damage, as well as forelimb grip strength and myofiber size. The administration of ZQ-SJZ also significantly prolonged the survival of LLC-induced cachectic mice under cisplatin treatment. Mechanistically, ZQ-SJZ increased the levels of myogenic proteins, such as myosin heavy chain (MyHC) and myogenin, and decreased the atrophy-related protein, atrogin-1, in cisplatin-treated C2C12 myotubes in vitro. In addition, cisplatin-induced mitochondria dysfunction could be hampered by the co-administration of ZQ-SJZ, by which it recovered the cisplatin-mediated decrease in PGC-1α and PKM1 levels. Conclusions: The administration of ZQ-SJZ can recover tumor- and/or cisplatin-induced cachectic conditions and significantly prolong the survival of LLC-induced cachectic mice under cisplatin treatment. The profound effect of ZQ-SJZ in hampering tumor- and/or cisplatin-induced cachexia may be due to its modulation of the mitochondrial function and subsequent myogenesis. Taken together, these results demonstrated the anti-cachectic mechanism of ZQ-SJZ and its potential use as a palliative strategy to improve the efficacy of chemotherapy. Graphical abstract: fx1